Experience of the USA and European Countries in Improving the Quality of Physical Education and Sports Education - Farkhod Turdalievich Abdullaev (Global Scientific Publishing, 2022)
The article describes what results the use of foreign experiences in the development of sports education can bring us today. Conclusions are presented as a result of studying the sports education system of foreign countries. It was emphasized that physical education and sports are important in ensuring health and active lifestyle at all stages of human life
Keywords: sports; hygienic requirements; educational system in France; physiological development